2018
DOI: 10.5430/ijhe.v7n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of College and University Choice for High-School Students in Qatar

Abstract: This paper investigates various predictors of high school students' college and university choice decisions in Qatar. Based on a 2015 survey of 1,427 participants, this study utilized exploratory factor analysis to identify variables that affect student choice of higher educational institutions (HEI). Three factors were extracted from the analysis, revealing the following aspects of the academic experience as important when choosing a HEI: i) quality of education; ii) cultural values; and iii) the cost of educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…The overall mean score suggests that most of the respondents seemed to agree that all the attributes related to the cost of education, degree (content and structure), physical aspects, facilities and resources, the value of education and course, and career information are important factors considered by the students in selecting the best university to further their study. Therefore, it can be concluded that the outcomes of the present are consistent with past literature which has successfully proven the importance and capability of the above-mentioned factors in influencing students' choice of higher education institution (Loren & Naltan, 2014;Cubillo et al, 2006;Ancheh et al, 2007;O'Brien et al, 2007;Wagner & Fard, 2009;Padlee et al, 2010;Abeygunawardena, 2018;Holmegaard, et al, 2014;Vulperhorst et al, 2020;Fernandez, 2010;Sia, 2011;Jalaluddin et al, 2019;Yusuf et al, 2017;Eidimtas et al, 2014;Sidin et al, 2003;Agrey et al, 2014;Mustafa et al, 2018;Hussin et al, 2019;Ariffin et al, 2014;Sia, 2013). In addition, public universities especially UiTM is known to offer a special track to Orang Asli which allows them to further their study at the university.…”
Section: Discussionsupporting
confidence: 87%
“…The overall mean score suggests that most of the respondents seemed to agree that all the attributes related to the cost of education, degree (content and structure), physical aspects, facilities and resources, the value of education and course, and career information are important factors considered by the students in selecting the best university to further their study. Therefore, it can be concluded that the outcomes of the present are consistent with past literature which has successfully proven the importance and capability of the above-mentioned factors in influencing students' choice of higher education institution (Loren & Naltan, 2014;Cubillo et al, 2006;Ancheh et al, 2007;O'Brien et al, 2007;Wagner & Fard, 2009;Padlee et al, 2010;Abeygunawardena, 2018;Holmegaard, et al, 2014;Vulperhorst et al, 2020;Fernandez, 2010;Sia, 2011;Jalaluddin et al, 2019;Yusuf et al, 2017;Eidimtas et al, 2014;Sidin et al, 2003;Agrey et al, 2014;Mustafa et al, 2018;Hussin et al, 2019;Ariffin et al, 2014;Sia, 2013). In addition, public universities especially UiTM is known to offer a special track to Orang Asli which allows them to further their study at the university.…”
Section: Discussionsupporting
confidence: 87%
“…Students in this small sample tended to display an instrumental connection between education and job-readiness. This instrumental connection and correlation between academic pursuits and employment contrasts with the Mustafa et al (2018) study of Qatari students who valued the quality of education, cultural values and academic costs as key factors towards their academic choices. Further, this instrumental connection to employability could be as a result of Finance students adopting a return-on-investment mindset (finance concept) towards their education.…”
Section: Discussionmentioning
confidence: 79%
“…This study reinforces that student perception of private for-profit HEIs is an important factor in influencing student choice to study at the institution. In a study in Qatar by Mustafa et al (2018), exploratory factor analysis was adopted to identify variables that affect students' decision-making process for choice of HEIs. Three factors were extracted from the analysis as important when choosing an HEI, namely, (1) quality of education; (2) cultural values; and (3) the cost of education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study reinforces that student perception of private for-profit HEIs is an important factor in influencing student choice to study at the institution. In a study in Qatar by Mustafa et al. (2018), exploratory factor analysis was adopted to identify variables that affect students' decision-making process for choice of HEIs.…”
Section: Literature Reviewmentioning
confidence: 99%